Genetic insights into forensic features and population structure of the Hajong tribe in the Indian regions of Eastern Himalaya - Vahinde, Avinash; Niranjan, Penny H.; Priyank, Gaurav; Niji, Chubi; Sahajpal, Vivek; Rana, Ajay S.; Bhandari, Deepika; Kumar, Satish; Nidhi, Sweta; Singh, Abhishek (Molecular genetics and genomics : MGG, 2025)
India’s northeastern region, particularly Meghalaya, a melting pot of diverse ethnic and racial groups that have been shaped by ancient migrations and the natural barriers posed by the Himalayas. The Hajong tribe, who live mainly in the Garo Hills of Meghalaya, reflect this diversity, sharing cultural similarities with the Tibetan and Bhutanese populations. Historically regarded as immigrants to Arunachal Pradesh, the Hajongs’ genetic relationship with the greater Himalayan region makes them an ideal subject for estimation of genetic attributes. This study analyzed 23 autosomal STR markers to assess the genetic diversity of Hajong tribe with emphasis on forensic parameters. Among the 23 autosomal STR markers analyzed, several loci including SE33, FGA, and D18S51 exhibited high polymorphic information content and paternity index values, reflecting their strong forensic utility in the Hajong population. The combined Power of Exclusion (PE) and Power of Discrimination (PD) was 0.999999999 and 0.999999999, respectively, whereas the Total Paternity Index (TPI) and the Combined Matching Probability (PM) was 756014064.7 and 1.3214E-27. The fixation index, F = − 0.016 ± 0.014, showed very minimal intra-population differentiation. Genetic relationship assessment, including NJ dendrograms and MDS plots, revealed a close genetic affinity between Hajong and populations from Tibet, Bhutan, Nepal, and Myanmar, reflecting a shared ancestral relationship. STRUCTURE analysis revealed well-defined clustering, with limited admixture in the Hajong population, indicating genetic distinctiveness. This study reflects the genetic individuality of the Hajong tribe and its utility for forensic studies in kinship analysis. Such studies will, further, help in analyzing population dynamics in Northeast India by tracing the history of migration and interrelationships among Himalayan populations.